Residência-arte: vai passar como uma proposição poética-estética-ética de uma artista - Borenstein, Malka Celina (2023)
Art-Residence: Vai Passar as an artist's poetic proposition is an interdisciplinary investigation that correlates the fields of communication and semiotics, art and politics. The dissertation proposes a critical and artistic reflection on the dimensions of construction of regimes of meaning, presence and collectivity, and other aestheticpolitical ways of being, in order to think of the practice of an artistic residence as an art-residence. This research is theoretical-practical and intends to investigate another possible aesthetic of residence from an experimental proposal operated by Christine Mello's extremities approach (2008) and the vectors of relaxation, contamination and sharing. As a result, works carried out through artistic practices with the ResidênciaArte Vai Passar will be presented. A dialogue is opened with the researcher Cecília Almeida Salles and her books Gesto inacabado: processo de criação artística (1998) and Redes de criação: construção da obra de arte (2006) to: (i) analyze possible transformations in the regimes of sense of presence in the context of artistic residencies; and (ii) think of another form of artistic residency, based on the assumption that it is possible to propose a residency as an artistic experiment, with aesthetic concerns, in addition to political implications. Throughout the process, the research expands to some thoughts of other aesthetics in the visual arts, which will be better developed in the course of writing, where authors who develop concepts around the themes will be approached: collective agency, sharing of the sensitive, creation networks, online social communities and artist residencies. Such as, Félix Guattari, Jacques Rancière, Priscila Arantes, Yara Guasque, Cláudio Bueno and João Simões